STRATEGI PENGEMBANGAN DESA WISATA SINDANGKASIH DI KABUPATEN GARUT - Muhammad Reynaldi Aulia Rahmat; Evi Novianti; Yustikasari Yustikasari (Media Bina Ilmiah, 2022)
Garut Regency as presenting rural tourism because it has the potential for natural beauty, culture, history. One of the tourist villages that has tourism potential is Sindangkasih Tourism Village. The Sindangkasih Tourism Village which was just inaugurated in 2019 needs to improve quality as a tourist village so that tourists are more interested in visiting. Therefore, the purpose of this research is to develop the tourism potential in Sindangkasih Tourism Village. The research was conducted directly through observation and interviews with managers and the community who knew the conditions in the tourist village. The results of this study discuss the need to develop tourism potential in Sindangkasih Tourism Village. Aspects that need to be developed related to the 6A tourism component include Attraction, Facilities, Ancillary, Activity, Accessibilities and Available Packages. Development through these 6 (six) aspects can be carried out in collaboration with related parties such as managers, communities, government, as well as entrepreneurs, academics